Strengthening Pancasila and Rahmatan lil Alamin student profiles: An inquiry of two Islamic vocational high schools - Sahibe, Nurhayati; Ilham, Abrari; Nurmanita, Mutiara; Daniaty, Maria; Sugiharto, Muh. Afif (Indonesian Research Journal in Education |IRJE|, 2025)
This research used a qualitative approach with a multi-site research design, which aimed to explore best practices and strategies implemented in each madrasa and identify factors that support and hinder the optimization of P5RA. Through this multi-site analysis, a more comprehensive understanding can be obtained regarding implementing these two profiles. The results of the research show that both the Madrasah Aliyah Kejuruan Madani Manado and the Madrasah Aliyah Kejuruan Negeri Bolaang Mongondow have demonstrated a strong commitment to instilling the values ​​of Pancasila and Rahmatan lil Alamin in students. Although both have the same goal, the approaches they use are different. Madrasah Aliyah Kejuruan Madani Manado, with vocational characteristics of nursing, places more emphasis on character development through project-based learning and collaboration with the world of health work. On the other hand, the Madrasah Aliyah Kejuruan Negeri Bolaang Mongondow, with its focus on agriculture, emphasizes the relevance of Pancasila values ​​in the context of agricultural practices.